Multimarker Augmented Reality in Human Digestive System Application Using the MDLC Method - Nugroho, Bagas Julio; Cahyono, Nuri (Jurnal Teknologi Informasi dan Pendidikan, 2024)
Learning media has a crucial role in supporting the learning process, especially in subjects related to natural sciences. Using conventional media such as blackboards, pictures in books, and less varied teaching methods can make students feel bored, less active, and lose concentration. Therefore, this research aims to implement augmented reality technology in science subjects to create exciting and memorable learning experiences for students and encourage student involvement in the learning process. This research uses the Multimedia Development Life Cycle (MDLC) method, which applies the latest technology, Multimarker, to display more than one three-dimensional (3D) object. The research results show that learning media using Augmented Reality Technology on the human digestive system obtained a “Good” predicate and can be used in the learning process at Tuguran State Elementary School.